2003
DOI: 10.1073/pnas.2635903100
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain abnormalities in young adults at genetic risk for late-onset Alzheimer's dementia

Abstract: Fluorodeoxyglucose positron emission tomography (PET) studies have found that patients with Alzheimer's dementia (AD) have abnormally low rates of cerebral glucose metabolism in posterior cingulate, parietal, temporal, and prefrontal cortex. We previously found that cognitively normal, late-middle-aged carriers of the apolipoprotein E 4 allele, a common susceptibility gene for late-onset Alzheimer's dementia, have abnormally low rates of glucose metabolism in the same brain regions as patients with probable AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
701
4
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 905 publications
(752 citation statements)
references
References 66 publications
41
701
4
6
Order By: Relevance
“…Nevertheless, these investigations did not prompt widespread adoption of IDIF and, indeed, the number of clinical research protocols using IDIF as a tool to reduce invasiveness in patients is very limited. Chen et al used their IDIF method for [ 18 F]-FDG (Chen et al, 1998) to measure cerebral metabolic rate for glucose in young adults at genetic risk for late-onset Alzheimer's dementia (Reiman et al, 2004), to differentiate healthy subjects from Alzheimer's patients (Chen et al, 2006), and to evaluate healthy adults reporting dream-enactment behaviors (Caselli et al, 2006). Schiepers et al used an IDIF method based on factor analysis to study patients with brain tumors using [ 18 F]-fluorothymidine (Schiepers et al, 2007b) and [ 18 F]-FDOPA (Fueger et al, 2010;Schiepers et al, 2007a).…”
Section: How Often Is Image-derived Input Function Used In Positron Ementioning
confidence: 99%
“…Nevertheless, these investigations did not prompt widespread adoption of IDIF and, indeed, the number of clinical research protocols using IDIF as a tool to reduce invasiveness in patients is very limited. Chen et al used their IDIF method for [ 18 F]-FDG (Chen et al, 1998) to measure cerebral metabolic rate for glucose in young adults at genetic risk for late-onset Alzheimer's dementia (Reiman et al, 2004), to differentiate healthy subjects from Alzheimer's patients (Chen et al, 2006), and to evaluate healthy adults reporting dream-enactment behaviors (Caselli et al, 2006). Schiepers et al used an IDIF method based on factor analysis to study patients with brain tumors using [ 18 F]-fluorothymidine (Schiepers et al, 2007b) and [ 18 F]-FDOPA (Fueger et al, 2010;Schiepers et al, 2007a).…”
Section: How Often Is Image-derived Input Function Used In Positron Ementioning
confidence: 99%
“…14 The regional reductions in CMRglc in AD may be due to reduction in the density or activity of terminal neuronal fields or glial cells, a metabolic defect within neurons or glia, or a combination of these factors. In a series of experiments, Reiman et al 15 examined the onset of hypometabolism in nondemented subjects at risk for AD. In an early study, Reiman et al 12 screened subjects between the ages of 50 and 65 years of age with a family history of AD for those who were homozygous for the E4 allele, and therefore at high risk of developing AD.…”
Section: Glucose Metabolism In Admentioning
confidence: 99%
“…The homozygotes and controls did not differ in any cognitive test, yet the E4/E4 homozygotes showed declines in glucose metabolism in the same regions identified in AD subjects. 12 In a follow-up study examining young adults, 15 12 E4 carriers (E4/E3) were compared with 15 E4 noncarriers. Similar to the previous study, E4 carriers (E4(ϩ)) were found to have low CMRglc bilaterally in the posterior cingulate, parietal, temporal, and prefrontal cortex, despite showing no signs of cognitive impairment.…”
Section: Glucose Metabolism In Admentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo preclinical AD models indicate that deficits in mitochondrial function, metabolic enzyme expression and activity, cerebral glucose metabolism, and free radical scavenging are coupled with mitochondrial Aβ load and Aβ-binding alcohol dehydrogenase (ABAD) expression [12,13,24,25]. Importantly, clinical studies indicate that mitochondrial deficits observed in preclinical models are evident in human-derived platelets [14,15,[26][27][28][29]. The antecedent decline in mitochondrial function and brain metabolism indicates an early and potentially causal role in AD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%